Short- and long-term outcomes of out-of-hospital cardiac arrest following ST-elevation myocardial infarction managed with percutaneous coronary intervention - Dawson, L.P.; Dinh, D.; Duffy, S.; Brennan, A.; Clark, D.; Reid, Christopher; Blusztein, D.; Stub, D.; Andrianopoulos, N.; Freeman, M.; Oqueli, E.; Ajani, A.E. (ELSEVIER IRELAND LTD, 2020)
© 2020